Research on Application of Dredging Technology for Steel Pipe Pile Under Complex Sea Conditions in Deep Sea - Jianjun CHEN (南方能源建设)
[Objective] With the promotion of carbon peak and carbon neutrality strategy, offshore wind power has ushered in a period of rapid growth. In 2023, more than 87 offshore wind power project sites in various provinces and cities across the country have identified investment entities or are carrying out project competition, with an installed capacity of more than 58.9 GW. In the future, the deep-sea foundation type will be mainly based on the four-pile jacket foundation, In the process of steel pipe pile penetrating, the surrounding soil will be disturbed, resulting in silt deposit. If the dredging outcome is not ideal, it will affect the strength of the infrastructure, on the other hand, it will affect the safety of fan hoisting. [Method] The article took a demonstrative wind farm in the East Guangdong Sea as an example. Firstly, this paper analyzed the causes and hazards of silt deposit in view of the characteristics of the wind farm, such as high water depth, poor visibility, high viscosity and large amount of silt removal. Secondly, combined with the successful application of the demonstrative project, the feasibility of the dredging process was verified. Finally, the dredging process could be further improved from three aspects: process optimization, equipment optimization and design optimization. [Result] Research has shown that the dredging method is optimized by ultra-high pressure hydraulic dredging and air disturbance dredging, the dredging equipment is optimized by robot technology, the elevation of pile top mud surface is adjusted and the rising space of silt is reserved for design optimization. The improved dredging process adapts to the complex conditions in deep sea, and further effectively improves the efficiency of underwater dredging. [Conclusion] The improved dredging process can be popularized and applied to subsequent deep-sea wind power projects.